Thresholds in aridity and soil carbon-to-nitrogen ratio govern the accumulation of soil microbial residues - Zhiguo Hao (Nature Portfolio, 2021)
Aridity, soil nutrient stoichiometry and bulk carbon content are reliable predictors of microbial residue accumulation in soil carbon pools, according to a meta-analysis of amino sugar concentrations in grasslands, woodlands and forests.